PENGARUH PERENCANAAN PAJAK, UKURAN PERUSAHAAN, DAN KEPEMILIKAN MANAJERIAL TERHADAP MANAJEMEN LABA - Melinda, Vani; Onasis, Dini; Apriliyani, Ika Berty (Jurnal Akuntansi Kompetif, 2024)
This study aims to examine the effect of tax planning, company size, and managerial ownership on earnings management. The data used in this study come from secondary data. The population of this study consists of 52 companies in the transportation sector listed on the Indonesia Stock Exchange during the period 2019 to 2021. The research sample was selected through purposive sampling technique according to certain criteria, which resulted in 16 companies as samples. The analytical method used in this research is multiple linear regression. To measure earnings management practices, the Jones Model Modification (Dechow et al, 1995) is used with the measurement of discretionary accruals (DA). The results of this study state that tax planning, firm size, and managerial ownership simultaneously have a significant effect on earnings management. Partially, hypothesis testing of tax planning variables shows a negative and significant effect on earnings management. Meanwhile, company size and managerial ownership variables have a positive and significant effect on earnings management.